Решите: 2см 5мм+5см= 7м3дм+2дм= 65м6дм-60м= 2м7дм-6дм= 13дм+4дм8см= 16м30см-6см= 70дм3см+3дм= 12дм9см-3дм=                                

Решите: 2см 5мм+5см= 7м3дм+2дм= 65м6дм-60м= 2м7дм-6дм= 13дм+4дм8см= 16м30см-6см= 70дм3см+3дм= 12дм9см-3дм=                                
Гость
Ответ(ы) на вопрос:
Гость
2см 5мм+5см=7см5мм 7м3дм+2дм=7м5дм 65м6дм-60м=125м6дм 2м7дм-6дм=2м1дм 13дм+4дм8см=17дм8см 16м30см-6см=16м24см 70дм3см+3дм=73дм3см 12дм9см-3дм=9дм9см
Гость
7см 5мм 7м 5дм 5м 6дм 2м 1дм 8см 17дм 16м 24см 73дм 3 см 9дм 9см
Не нашли ответ?
Ответить на вопрос
Похожие вопросы